Penguatan Nilai Multikultural Dalam Pendidikan Agama Islam Untuk Meningkatkan Karakter Siswa di Era Merdeka Belajar - Yanti Yulianti (putrapublisher.org, 2023)
The aim of this research is to illustrate the strengthening of multicultural values in Islamic religious education to improve student character in the era of independent learning. This research uses a qualitative approach with the library research method. Data sources use journal and book studies related to multicultural education. The results of this research are that strengthening multicultural values is an educational strategy that is applied to all types of subjects by using the cultural differences that exist in students such as differences in ethnicity, religion, language, gender, social class, race, ability and age so that the process learning becomes effective and easy. Islamic religious education in schools is designed to equip students to have a religious attitude and form and develop Islamic religious values and akhkalkul karimah.